METHODS OF REDUCING INFLAMMATORY COMPLICATIONS IN COMPLEX TOOTH EXTRACTION PROCEDURES - Karimov Akobir Bahodirovich (Web of Journals Publishing, 2025)
This article examines modern clinical and preventive approaches aimed at reducing inflammatory complications following complex tooth extraction procedures. The study analyzes the main etiological factors contributing to postoperative inflammation—such as traumatic tissue injury, microbial contamination, and impaired local microcirculation—and evaluates the effectiveness of combined therapeutic methods including atraumatic surgical techniques, antiseptic irrigation, antibiotic prophylaxis, and low-level laser therapy. Clinical observations among 120 patients undergoing complex extractions revealed that the use of atraumatic instruments, local antiseptics, and photobiomodulation significantly decreased the incidence of alveolitis and edema by 45%. The findings demonstrate that the integration of evidence-based surgical protocols and physiotherapeutic adjuncts enhances wound healing, minimizes pain, and ensures safer recovery in oral surgery practice.
Keywords: Complex tooth extraction, postoperative inflammation, alveolitis, prevention, low-level laser therapy, antiseptic irrigation, surgical dentistry, wound healing.